Raton navyman travels world, but loves home (Raton Range Raton, New Mexico, 1984)
Newspaper Article on Naval boatswain's mate Jeffrey D. Skinner and his experience on the USS independence and his love for his home town of Raton, New Mexico.
Master list item #: 8
File location is in the Raton File Cabinet
Keywords: Skinner, Jeffrey D; Skinner, Robert; Skinner, Mary Jean; U.S. Navy; Local History; Biography; Life and Customs; USS Independence; USS John F. Kennedy; Shipmates; Deployment; Air Crafts; Safety department; Raton, New Mexico; Norfolk, Virginia; Grenada; Lebanon; Asia; Europe; The Mediterranean; Middle East; South America; Australia; Egypt